A checklist and conservation status of vascular plants in the Limestone forest of Metropolitan Ilocos Norte Watershed Forest Reserve, Northwestern Luzon, Philippines - Mae Ann Batuyong; MICHAEL A. CALARAMO; GRECEBIO JONATHAN D. ALEJANDRO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Batuyong MAR, Calaramo MA, Alejandro GJD. 2020. A checklist and conservation status of vascular plants in the Limestone forest of Metropolitan Ilocos Norte Watershed Forest Reserve, Northwestern Luzon, Philippines. Biodiversitas 21: 3969-3981. The Metropolitan Ilocos Norte Watershed Forest Reserve (MINWFR) is among the remaining intact limestone formations and a critical protected area in Northwestern Luzon. There have been few published floristic studies despite its undeniable rich biological importance. Therefore, this paper primarily aims to provide a preliminary checklist of vascular plants in MINWFR and their conservation status.  Consequent field visits and surveys were made from April 2019 to March 2020. Results revealed a total of 173 species distributed in 140 genera belonging to 59 families. The most represented families are Rubiaceae, Fabaceae, Orchidaceae, and  Malvaceae. This forest supports 49% or 28.65 % local endemics, five of which are narrow endemics, namely Cyanometra warburgii, Pyrostria triflora, Syzygium ilocanum, Thrixspermum nicolasiorum, and Antirhea microphylla. The latter, however, extends up to Ilocos Sur. Based on IUCN criteria and DENR records, a total of 18 species are threatened, one species is recorded as critically endangered, five endangered, nine vulnerable, three other threatened, two near threatened, 55 as least concern, and the rest are not evaluated. Other noteworthy species present in the area are the two dominant endangered species, Podocarpus costalis, and Podocarpus polystachyus. An interesting spinescent Rubiaceae species were recorded and currently under examination to establish its identity. This checklist serves as a basis to effectively manage this vulnerable area surrounded by human-induced disturbances and threats.